Causes of permanent vertical deformation at subduction margins: Evidence from late Pleistocene marine terraces of the southern Hikurangi margin, Aotearoa New Zealand - Ninis, Dee; Howell, Andy; Little, Timothy; Litchfield, Nicola (Frontiers in Earth Science, 2023)
Theoretical studies of the seismic cycle at convergent plate boundaries anticipate that most coseismic deformation is recovered, yet significant permanent vertical displacement of the overriding plate is observed at many subduction margins. To understand the mechanisms driving permanent vertical displacement, we investigate tectonic uplift across the southern Hikurangi subduction margin, Aotearoa New Zealand, in the last ∼200 ka. Marine terraces preserved along the Wellington south coast have recently been dated as Marine Isotope Stage (MIS) 5a (∼82 ka), 5c (∼96 ka), 5e (∼123 ka) and 7a (∼196 ka) in age. We use these ages, together with new reconstructions of shoreline angle elevations, to calculate uplift rates across the margin and to examine the processes responsible for their elevation. The highest uplift rate—1.7 ± 0.1 mm/yr–and maximum tilting—2.9° to the west–are observed near Cape Palliser, the closest site to (∼50 km from) the Hikurangi Trough. Uplift rates decrease monotonically westward along the Palliser Bay coast, to 0.2 ± 0.1 mm/yr at Wharekauhau (∼70 km from the trough), defining a gently west-tilted subaerial forearc domain. Locally, active oblique-slip upper-plate faults cause obvious vertical offsets of the marine terraces in the axial ranges (>70 km from the trough). Uplift rates at Baring Head, on the upthrown side of the Wairarapa-Wharekauhau fault system, are ∼0.7–1.6 mm/yr. At Tongue Point, uplift on the upthrown side of the Ōhāriu Fault is 0.6 ± 0.1 mm/yr. Dislocation and flexural-isostatic modelling shows that slip on faults within the overriding plate—specifically the Palliser-Kaiwhata Fault and the Wairarapa-Wharekauhau fault system—may dominate uplift in their immediate hanging walls. Depending on their slip rate and geometry, slip on these two upper-plate fault systems could plausibly cause >80% of late Pleistocene uplift everywhere along the south coast of North Island. Our modelling suggests that subduction of the buoyant Hikurangi Plateau contributes uplift of 0.1–0.2 mm/yr and uplift due to sediment underplating at Tongue Point and Wharekauhau is likely ≤0.6 mm/yr but could be significantly lower. Earthquakes on the subduction interface probably contribute ≤0.4 mm/yr of late Pleistocene uplift, with ≤10% of uplift due to each earthquake being stored permanently, similar to other subduction zones. These results indicate a significant contribution of slip on upper-plate faults to permanent uplift and tilting across the subduction margin and suggest that in regions where upper-plate faults are prevalent, strong constraints on fault geometry and slip rate are necessary to disentangle contributions of deeper-seated processes to uplift.